Literasi Mahasiswa BIPA Program Darmasiswa Universitas Ahmad Dahlan Bermuatan Bahasa dan Budaya Indonesia - Sudaryanto Sudaryanto; Hermanto Hermanto; Luluk Mahdhuroh; Muhammad Alfian Hermawan; Azkiya Zelfi Xirana (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2018)
The interest in learning foreign students about Indonesian is high. This can be seen at least from the number of foreign students studying at the Ahmad Dahlan University Darmasiswa Program (UAD), especially in the 2016/2017 academic year (TA). This fact is certainly interesting to study more considering that Indonesian Language for Foreign Speakers (BIPA) is a rapidly developing scientific field. The purpose of this study is to describe the literacy of BIPA UAD Darmasiswa Program containing Indonesian language and culture. The method of collecting data in this study is the observation method with the technique of reading and recording. Data is taken from photos and descriptions of lecture activities in the classroom and outside the UAD Darmasiswa Program class. The results of this study indicate that BIPA student literacy The UAD Darmasiswa Program with Indonesian language and culture is carried out inside and outside the classroom. Activities in the classroom include lectures on Indonesian language skills and culture, while activities outside the classroom include mankakrida activities at Borobudur Temple, Imogiri Tomb, Chocolate Monggo Factory, Batik Mekar, and others. With these activities, the BIPA Darmasiswa UAD students became more aware of Indonesian language and cultural knowledge and skills.